PENGARUH NILAI DAN KEPERCAYAANTERHADAP KOMITMEN AFEKTIF: STUDI KAUSAL TERHADAP GURU DI SEKOLAH BOGOR RAYA A NATIONAL PLUS, BOGOR - Willfridus Demetrius Siga; Komarudin Komarudin (Jurnal Computech & Bisnis (e-Journal), 2018)
The objective of research is to find out influences of the Values and Trust toward the teachers affective in Sekolah Bogor Raya. The research using a survey method with causal technique. This research used as a sample of 94 teachers as respondents. The samples are selected based on standard error technique. The study was a causal survey using path analysis. Technique data collecting was using the instrument in the form of questionnaire. The result showed that, 1) there is a direct influences of values toward affective commitment, 2) there is a direct influences of trust toward affective commitment, 3) there is a direct influences of values toward trust, 4) there is undirect influences of values toward affective commitment by the trust. The implication of this research is an effort in improving the affective commitment of the teachers can be done through values and trust.Keywords: values, trust, affective commitmentDOI 10.5281/zenodo.3373744